Karakteristik Klinis dan Demografi Pasien Infark Miokard Elevasi ST di Siloam Heart Center: A Single Center Study - Laksono, Sidhi; Nurbaeti, Putri (Majalah Kedokteran Indonesia, 2025)
Introduction: Cardiovascular disease remains the leading cause of death globally, with ST-elevation myocardial infarction (STEMI) posing the highest mortality among acute coronary syndromes (ACS). Early intervention, such as percutaneous coronary intervention (PCI), improves outcomes. Objective: To describe the clinical and demographic profile of STEMI patients in Indonesia and identify risk factors associated with disease severity.Methods: A retrospective descriptive study was conducted on STEMI patients who underwent PCI at a Heart Center Hospital from January to December 2024. Data from electronic medical records were analyzed, including only confirmed STEMI cases with complete documentation.Result: 87 patients were included, most male (92%) and aged over 50 (66.7%). Hypertension (49.4%), smoking (46%), and diabetes mellitus (27.6%) were common comorbidities. Leukocytosis occurred in 86.2%, with universally elevated troponin levels. Despite frequent cardiomegaly on chest X-rays, 46% had preserved ejection fraction on echocardiography. Inferior (34.5%) and anterior (19.5%, 17.2%) infarctions were the most common ECG findings. The left anterior descending (LAD) artery was affected in 85.1%, with three-vessel disease present in 49.4%. Mean door-to-balloon (DTB) time was 86.25 minutes. In Intra-PCI Complications, dissection in 2.3%.Conclusion: STEMI in Indonesia predominantly affects older males with modifiable cardiovascular risk factors. These factors are closely linked to severe coronary involvement, particularly multi-vessel disease.